Who benefits from the green transition? energy justice and community ownership in rural renewable energy initiatives - Suaidi (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Rural renewable energy initiatives are increasingly central to Indonesia’s green transition, yet their social value depends on whether benefits, costs, decisions, and ownership responsibilities are distributed fairly among community members. Objective: This community engagement program aimed to strengthen energy justice and community ownership in Desa Andungbiru by mapping local energy benefits, preparing participatory governance tools, and supporting community-led monitoring of renewable energy use. Method: Methodologically, this program combined participatory planning, climate and energy literacy orientation, citizen science training, community observation, validation forums, micro-adaptation mentoring, and monitoring-evaluation involving village authorities, energy managers, women’s groups, youth, farmers, and productive users. Results: Planning activities produced partner coordination records, needs assessment tools, stakeholder maps, justice-oriented instruments, a monitoring schedule, and a reflection forum design. Implementation activities documented orientation activities, citizen observation practices, reporting templates, validation meetings, community reflection, and small-scale action plans for productive and household energy use. Implication: Monitoring-evaluation activities reviewed participation, assessed capacity indicators, audited data quality, validated community findings, and drafted sustainability mechanisms for continued local oversight. Novelty: The novelty of this program lies in reframing rural renewable energy assistance beyond infrastructure delivery alone as a community-owned energy justice audit that integrates local knowledge, citizen-generated data, transparent governance, and adaptive capacity collectively for villages.